Through the lens of the romantic child: portraits of children by Mark Hipper and Terry Kurgan - Evans, Judith Marian (My University, 2016)
This research report explores how the eighteenth century Romantic Child Ideal influenced the representations of children created by artists Terry Kurgan and Mark Hipper, and subsequently what the responses to these works reveal about a relationship to and participation in the ideal within the context of South Africa in the late 1990s. Through a close reading of two seminal exhibitions, the group show Purity and Danger (1997) which featured Terry Kurgan’s photographs of her son, and Vicera (1998) Mark Hipper’s mixed media offering of child nudes, I analysed the manner in which these artists both perpetuate and subvert the Ideal through their specific visualisations of the child.
Thesis (M.A (History of Art))--University of the Witwatersrand, Faculty of Humanities, School of Arts, 2016
Keywords: Hipper, Mark--Exhibitions; Kurgan, Terry; Children in art; Children--Portraits